Investigating the pathogenesis of high‐serum gamma‐glutamyl transferase activity in Thoroughbred racehorses: A series of case‐control studies. (8th March 2021) - Mann, Sabine; Ramsay, Joshua D.; Wakshlag, Joseph J.; Stokol, Tracy; Reed, Steven; Divers, Thomas J.
Abstract: Background: High‐serum γ‐Glutamyl Transferase (GGT) activity has been associated with and thought to be a marker of maladaptation to training and possibly poor performance in racehorses, but the cause is unknown. Objectives: To investigate possible metabolic and infectious causes for the high GGT syndrome. Study design: Pilot case‐control study and nested case‐control study. Methods: The case‐control study in 2017 included 16 horses (8 cases and 8 controls with median [range] serum GGT 82 [74‐148] and 22 [19‐28] IU/L, respectively) from the same stable. In 2018, similar testing was performed in a nested case‐control study that identified 27 case (serum GGT 50 ≥ IU/L)‐control pairs from three stables for further testing. Serum liver chemistries, selenium measurements, viral PCR and metabolomics were performed. Results: No differences were found in frequency of detection of viral RNA/DNA or copy numbers for equine hepacivirus (EqHV) and parvovirus‐hepatitis (EqPV‐H) between cases and controls. Mild increases in hepatocellular injury and cholestatic markers in case vs control horses suggested a degree of liver disease in a subset of cases. Metabolomic and individual bile acid testing showed differences in cases compared with controls, including increased abundance of pyroglutamic acid and taurine‐conjugated bile acids, and reduced abundance of Vitamin B6. Selenium concentrations, although within or above the reference intervals, were also lower in case horses in both studies. Main limitations: Observational study design did not allow us to make causal inferences. Conclusions: We conclude that high GGT syndrome is likely a complex metabolic disorder and that viral hepatitis was not identified as a cause for this syndrome in this cohort of racehorses. Our results support a contribution of oxidative stress and cholestasis in its pathophysiology.